Hubungan Kepadatan Hunian dan Sosial Ekonomi dengan Kejadian Penyakit Tuberculosis Paru Studi Kasus di Wilayah Kerja Puskesmas Belakang Padang, Kelurahan Pecung Kecamatan Belakang Padang Kota Batam - Ice Irawati; Hengky Oktarizal; Ade Haryanto (Dinamika Lingkungan Indonesia, 2020)
One of the main factors causing the high rate of pulmonary tuberculosis is occupancy density and socioeconomic. The purpose of this study was to study the relationship of occupancy density and socioeconomic with the incidence of pulmonary tuberculosis in Pecung Subdistrict, Balakang Padang District, Batam City (Belakang Padang Community Health Center) in 2019.This study uses a cross-sectional study, the sampling technique uses simple random sampling where the sample is taken 90 samples, primary data is obtained by using questionnaire, data analysis by bivariate using chi-square test (>0.05).The results of this research about the relationship between Occupancy Density with Pulmonary tuberculosis a value of p = 0,000 (pV<0.05), and there is a Socio-Economy relationship with pulmonary tuberculosis disease with a value of p = 0,000 (pV> 0.05. Expected promotion health by community healthcenter For the community to increase awareness of life and a Healthy environment.